2010
DOI: 10.1182/blood-2010-02-267450
|View full text |Cite
|
Sign up to set email alerts
|

Specific N-linked glycosylation sites modulate synthesis and secretion of von Willebrand factor

Abstract: We examined the role that N-linked glycans play in the synthesis and expression of von Willebrand Factor (VWF). Blocking the addition of N-linked glycans (NLGs) or inhibiting initial glycan processing prevented secretion of VWF. To determine whether specific glycosylation sites were important, the 16 VWF N-linked glycosylation sites were mutated followed by expression in HEK293T cells. Four NLG mutants affected VWF expression: N99Q (D1 domain), N857Q (D' domain), N2400Q (B1 domain), and N2790Q (CK domain) eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 41 publications
2
53
0
2
Order By: Relevance
“…59 Although the molecular mechanism through which N-linked glycan determinants regulate coagulation glycoprotein clearance remains unknown, the effect may be due to general properties of the complex sugar chains or instead may be attributable to particular carbohydrate structures located at specific N-linked sites. 42,43 Given the role of the A1-A2-A3 domains in modulating the interaction of VWF with macrophages, we further investigated whether the 2 N-linked glycosylation sites located at N1515 and N1574, respectively, might play a particular role in regulating VWF clearance. Importantly, we observed that loss of N-linked glycans following site-directed mutagenesis at either N1515 or N1574 resulted in markedly enhanced clearance of full-length rVWF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…59 Although the molecular mechanism through which N-linked glycan determinants regulate coagulation glycoprotein clearance remains unknown, the effect may be due to general properties of the complex sugar chains or instead may be attributable to particular carbohydrate structures located at specific N-linked sites. 42,43 Given the role of the A1-A2-A3 domains in modulating the interaction of VWF with macrophages, we further investigated whether the 2 N-linked glycosylation sites located at N1515 and N1574, respectively, might play a particular role in regulating VWF clearance. Importantly, we observed that loss of N-linked glycans following site-directed mutagenesis at either N1515 or N1574 resulted in markedly enhanced clearance of full-length rVWF.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with previous studies defining the biological significance of these glycans, [42][43][44] each asparagine residue was mutated to glutamine (N1515Q and N1574Q) to eliminate the N-linked glycans at these positions. Mutations were verified by DNA sequencing to ensure the absence of any other randomly introduced mutations.…”
Section: Expression and Purification Of Recombinant Vwfmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 VWF N-linked glycans have been studied extensively, although the data on the role of VWF OLGs are limited and often contradictory. 16,17 VWF lacking O-glycans is synthesized, multimerized, secreted, and binds heparin and collagen type I in the same way as the fully glycosylated form. 18 We recently published a detailed study of the VWF O-glycome composition showing the presence of unusual disialosyl motifs and ABH-bearing core 2 structures.…”
Section: Introductionmentioning
confidence: 99%
“…8,12,13 The mechanism of formation of the VWF strings involves cysteine thiol/disulfide exchange, because the formation of the strings is inhibited by thiol alkylation 12 and the string structure is disrupted by the small thiol N-acetylcysteine. 14 Mature VWF, both purified from plasma and made recombinantly, contains unpaired cysteine thiols 12,[15][16][17] that have been localized to the N-terminal D3 and C-terminal C domains. 12,13,17 Presumably, one or more of these cysteine thiols is involved in VWF self-association.…”
Section: Introductionmentioning
confidence: 99%